DIGITAL PROSECUTION MANAGEMENT IN THE ERA OF SOCIETY 5.0: A STUDY OF THE YOUNG MEDAN PROSECUTION COMMUNITY - Ali Ansor Siregar; Abdurrahman Abdurrahman (Journal Analytica Islamica, 2025)
This study aims to analyze the digital da'wah management practices implemented by the Medan Muda Berdakwah community, a representative of an urban youth da'wah movement that adapts to socio-technological challenges. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and digital documentation, and analyzed using thematic analysis techniques. The results indicate that this community implements a structured digital da'wah strategy through three main stages: planning based on social trends and the Islamic calendar; implementing contextual, visual, and communicative content through Instagram, TikTok, and YouTube; and evaluating using data insights and audience engagement. Two-way communication practices and internal-external collaboration are key elements in strengthening the loyalty of digital congregations and creating a da'wah narrative that is moderate, inclusive, and relevant to the spiritual needs of digital natives. This study emphasizes the importance of integrating theological competence, technological skills, and communication strategies in managing digital da'wah. These findings provide theoretical contributions to the development of a network-based da'wah management model and provide practical implications for religious organizations in designing sustainable digital da'wah strategies amidst the complexities of the Society 5.0 era.